COVID-19 Pandemic: Age and Temperature Related Effects - Kaur, Gursharan; Singh, Amandeep; Narang, Raj K.; Singh, Gurmeet (Coronaviruses, 2021)
Background: Coronavirus belongs to the phylum Incertaesedis, Nidovirales order, Orthocononaviridae subfamily. and spring up from the family of viruses that can cause the common cold, fever, shortness of breath, aches, chills, loss of smell, etc. Objective: As we all know; coronavirus has affected the whole world, and many patients died due to it. As the prevalence of this disease has risen, many myths have also originated like the effect of temperature on the virus; is this virus surely killed by the effect of temperature? Is the effect of this virus is more on the old age patients? In the presented compilation, we have tried to exposé the actual reality behind these myths and also tried to find the morphological alteration of coronavirus from the other viruses. Methods: The recent updates on this virus have been obtained from search engines like Pub med and Google scholar, by using COVID-19, coronavirus, Pandemic corona keywords. Results: After a huge search on the temperature effect on this disease, it was evident that there is no effect of temperature on the coronavirus. Due to the immunity factor, it showed its worst effect on old age people in many countries. Conclusion: The structure, symptoms and incubation period of coronavirus have been described in this review article. We have summarized how the coronavirus is different from others, and the effects of temperature and old age have also been discussed.
Keywords: COVID-19